Era Baru â€œHutan Kecilâ€ Menara Telekomunikasi: Rekonstruksi Analisis Penghitungan Tarif Retribusi - Rasad, Syah; Hermanto, Hermanto; Animah, Animah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
The Constitutional Court overturned the calculation of levy tariff based on Nilai Jual Objek Pajak (NJOP) multiplied by 2%, so that the Regional Government in formulating the retribution levies to be guided by Pasal Â 151, Pasal 152 and Pasal 161, Law Number 28 Year 2009 on Pajak Daerah dan Retribusi Daerah (PDRD). This study aims to determine the determination of tariff Retribusi Pengendalian Menara Telekomunikasi (RPMT) after the decision of the Constitutional Court by calculating the allocation of costs based on the activity of tower control. The research method used in this research is qualitative case study, using descriptive analysis of interactive model. The research took place at the Department of Transportation of Communication and Informatics of Sumbawa Regency involving 7 informants. Methods of data collection is done by observation method, interview and collecting document in the form of photo and audio visual. The results showed that the determination of the RPMT tariff after the decision of the Constitutional Court was calculated based on the multiplication of the frequency of visits within a budget year by multiplication between the cost allocation based on the tower supervision activity and the zoning coefficient, tower height, tower type and mileage.